High dose intravenous steroid therapy for severe posterior segment uveitis in Behçet's disease - Toker, E (Copyright 2002 British Journal of Ophthalmology, 2002)
Aim: To evaluate the safety and effectiveness of high dose intravenous steroid therapy (HDIST) in Behçet's disease patients with severe posterior segment uveitis attacks. Methods: Five patients with ocular Behçet's disease were treated with HDIST for severe posterior segment attacks. Two patients had vasculitis, one patient had papillitis, and the other two had retinitis; four patients also had accompanying severe vitritis. The visual acuities and improvement in ocular signs after HDIST were evaluated. Results: During HDIST, patients had no systemic complications caused by treatment. All patients responded to HDIST with evidence of a decrease in intraocular inflammatory activity and improved visual acuities within a mean time of 7 (1–15) days of commencing treatment. During follow up three out of five patients had new posterior segment attacks. Conclusion: HDIST is effective in controlling severe, vision threatening acute posterior segment Behçet's uveitis attacks and in improving visual function in a short period of time